Comparisons Between Frontline Therapy and a Combination of Eltrombopag Plus Immunosuppression Therapy and Human Leukocyte Antigen-Haploidentical Hematopoietic Stem Cell Transplantation in Patients With Severe Aplastic Anemia: A Systematic Review - Yang, Yuan; Ji, Jiang; Tang, Zengwei; Han, Bing (Frontiers in Oncology, 2021)
Background & Aims: This study aimed at comparing the efficacy and safety of eltrombopag (EPAG) plus immunosuppressive therapies (IST) and haploidentical hematopoietic stem cell transplantation (haplo-HSCT) in the frontline treatment for severe aplastic anemia (SAA) patients. Methods: Four electronic databases and Clinicaltrials.gov were comprehensively searched from January, 2010 to August, 2020. Studies that aimed at evaluating the efficacy and safety of EPAG + IST or haplo-HSCT in SAA patients were included. 1/2-yr overall survival (OS), complete response (CR) and overall response rates (ORR) were indirectly compared between EPAG + IST or haplo-HSCT. Results: A total of 447 patients involved in 10 cohort studies were found to be eligible for this study. A narrative synthesis was performed due to lack of data directly comparing the outcome of EPAG+IST and Haplo-HSCT. Consistent with analysis results in the whole population, subgroup analyses in the age-matched population showed that there was no significant difference in ORR between EPAG+ IST and haplo-HSCT groups. However, the CR rate was lower in the EPAG+IST group when compared to the haplo-HSCT group. The incidence rate of clonal evolution/SAA relapse ranged from 8%~14% and 19%~31% in the EPAG+IST group, but not reported in haplo-HSCT group. The incidence rate for acute graft verse host disease (aGVHD) and chronic graft verse host disease (cGVHD) ranged from 52%~57% and 12%~67%, respectively for haplo-HSCT group. The main causes of deaths were infections in the EPAG+IST group,and GVHD and infections in haplo-HSCT group. Conclusion: EPAG+IST has a comparable ORR and 1-yr/2-yr OS but lower CR rate when indirectly compared to haplo-HSCT in the frontline treatment of patients with SAA. Patients treated with haplo-HSCT may exhibit a high incidence of GVHD whereas patients treated with EPAG+IST may experience more relapses or clone evolution.